A Metaphysics for Mathematical and Structural Realism - Gerard, Adam InTae (Stance: an international undergraduate philosophy journal, 2019)
The goal of this paper is to preserve realism in both ontology and truth for the philosophy of mathematics and science. It begins by arguing that scientific realism can only be attained given mathematical realism due to the indispensable nature of the latter to the prior. Ultimately, the paper argues for a position combining both Ontic Structural Realism and Ante Rem Structuralism, or what the author refers to as Strong Ontic Structural Realism, which has the potential to reconcile realism for both science and mathematics. The paper goes on to claims that this theory does not succumb to the same traditional epistemological problems, which have damaged the credibility of its predecessors.